Multinational study exploring patients' perceptions of side-effects induced by chemo-radiotherapy. Issue 2 (November 2015) - Ruhlmann, Christina H.; Iversen, Trine Zeeberg; Okera, Meena; Muhic, Aida; Kristensen, Gunnar; Feyer, Petra; Hansen, Olfred; Herrstedt, Jørn
Abstract: Purpose: We aimed to prospectively assess the incidence, severity and patients' perceptions of side-effects induced by radiotherapy and concomitant weekly cisplatin. Patients and methods: This multinational survey included patients with a diagnosis of gynaecological or head and neck cancer scheduled to receive radiotherapy and concomitant weekly cisplatin. Patients completed a questionnaire prior to anti-cancer treatment and after 3 weeks of treatment. Baseline frequency and severity of symptoms were compared to frequency and severity after 3 weeks of treatment, and patients were asked to rank the five most severe symptoms experienced. Results: An increase in the severity as well as in the mean number of symptoms (18 compared to 24) was observed during treatment. Patients ranked 7 of the 10 most feared baseline symptoms as non-physical, whereas 8 of the 10 most feared symptoms after 3 weeks of treatment were physical. Nausea was ranked as the 5th most severe symptom during treatment, despite 98% of patients receiving antiemetic prophylaxis. Conclusion: Patients with head and neck cancer or gynaecological cancer suffer from a number of primarily non-physical symptoms before starting combined chemo-radiotherapy. After 3 weeks of treatment patients score 8 of the 10 most feared symptoms as physical. Future trials focusing on the prevention of side-effects in patients receiving radiotherapy and concomitant chemotherapy are highly warranted.